The association of combined vitamin C and D deficiency with bone mineral density and vertebral fracture - Lei He; Kishor chhantyal; Zihao Chen; Ruijue Zhu; Liangming Zhang (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Purpose Both vitamin C and D deficiencies are extremely common in clinical practice, especially in elderly population. Unfortunately, the role of vitamin C deficiency in osteoporosis related consequences is often neglected. The aim of the present study is to analyse if combined vitamin C and D deficiency would have an association with bone mineral density (BMD) and osteoporotic vertebral fracture (OVF). Methods Ninety-nine post-menopausal female patients admitted in the department of spine surgery of third affiliated hospital of Sun Yat-sen University were enrolled in the study. The participants were divided into four groups; vitamin D deficiency alone (comparator group), vitamin C deficiency alone and combined vitamin C and D deficiency as experimental group. The levels of vitamin C, vitamin D, calcium, phosphorous, BMD and condition of OVF were analysed. Results There were statistically significant differences between the groups in terms of vitamin C and D levels. In terms of lumbar BMD, significant differences were observed between vitamin D deficiency alone and combined vitamin C and D deficiency. Only the combined vitamin C and D deficiency had a significant negative association with lumbar BMD and T-score. Similarly, combined vitamin C and D deficiency had a significant positive association with lumbar osteoporosis. None of the groups had any significant association with OVF. Combined vitamin C and D deficiency was found to be significantly associated with lower lumbar BMD and osteoporosis. Conclusion Combined vitamin C and D deficiency results in lower bone mineral density and higher risk of osteoporosis. We believe that existence of deficiencies of both vitamins could have a synergistic effect. Therefore, we recommend that vitamin C and D should be routinely measured in clinical practice.